Pencegahan Perkawinan Dini Melalui Program PIK-R: Studi Yuridis Efektivitas Pendewasaan Usia Perkawinan di Desa Curah Kalong, Jember - Nandya Sabilla Khoirun Nisya; Rina Suryanti (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
The purpose of the research is to be able to answer the problems in Curah Kalong Village, which is designated as an area with the highest rate of early marriage in Bangsalsari District, one of the efforts to reduce the number of early marriages with the PUP Program by PIK-R where this program provides understanding and awareness to teenagers so that they can plan their families carefully, including considering various aspects of life and determining the number and spacing of births by delaying marriage until a more mature age. This study uses an empirical legal research type with a sociological approach. Data collection techniques using observation, interviews, and documentation, the validity of the data in this study uses data triangulation techniques. The data source used is primary legal material in the form of Law No. 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning marriage, to support primary legal materials the researcher also uses secondary legal materials in the form of books, books, legal journals and the internet and is assisted by a guideline for managing the Youth Information and Counseling Center, the results of this study are: 1) The Marriage Age Maturation Program in Curah Kalong Village is implemented sustainably through counseling and the formation of PIK-R, involving counselors, village governments, and adolescents. The main focus is to foster adolescents to understand reproductive health, mental readiness, and the risks of early marriage as an effort to build shared awareness. 2) The Marriage Age Maturation Program is considered effective in preventing early marriage because it has succeeded in increasing adolescent understanding and significantly reducing the number of cases in Curah Kalong Village, especially in 2024. Keywords: Prevention, Early Marriage, PIK-R Program Abstrak : Tujuan Penelitian adalah dapat menjawab permasalahan di Desa Curah Kalong, yang ditetapkan sebagai daerah dengan tingkat perkawinan dini tertinggi di Kecamatan Bangsalsari, salah satu upaya untuk menekan angka perkawinan dini dengan Program PUP oleh PIK-R dimana Program ini memberikan pemahaman dan kesadaran kepada remaja agar dapat merencanakan keluarga secara matang, termasuk mempertimbangkan berbagai aspek kehidupan serta menentukan jumlah dan jarak kelahiran dengan cara menunda perkawinan hingga usia yang lebih dewasa. Penelitian ini menggunakan jenis penelitian yuridis empiris dengan pendekatan sosiologis. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi, keabsahan data dalam penelitian ini menggunakan Teknik triangulasi data. Sumber data yang digunakan ialah bahan hukum primer berupa Undang-Undang No 16 Tahun 2019 tentang Perubahan atas Undang-Undang Nomor 1 Tahun 1974 tentang perkawinan, untuk mendukung bahan hukum primer peneliti juga menggunakan bahan hukum sekunder berupa buku-buku, kitab, jurnal hukum dan internet serta dibantu dengan buku pedoman pengelolaan Pusat Informasi dan Konseling Remaja, hasil penelitian ini ialah : 1) Program Pendewasaan Usia Perkawinan di Desa Curah Kalong dilaksanakan secara berkelanjutan melalui penyuluhan dan pembentukan PIK-R, melibatkan penyuluh, pemerintah desa, dan remaja. Fokus utamanya adalah membina remaja agar memahami kesehatan reproduksi, kesiapan mental, dan risiko perkawinan dini sebagai upaya membangun kesadaran bersama. 2) Program Pendewasaan Usia Perkawinan dinilai efektif mencegah perkawinan dini karena berhasil meningkatkan pemahaman remaja dan menurunkan angka kasus secara signifikan di Desa Curah Kalong, terutama pada tahun 2024.